Analysis of the Relationship between Resilience and Stress in Hypertension Patients - Suraying; Lailatul Hafidah; Faisal Amir; Willi Holis; Mohammad Shiddiq Suryadi (Health and Technology Journal (HTechJ), 2024)
Hypertension is a non-communicable disease that often occurs in society, especially in developing countries. The inability to effectively control hypertension, especially when aggravated by stress, can result in a range of complications and ultimately fatal outcomes. Purpose: The aim of this research is to analyze strengthening resilience towards balancing psychological stress in hypertensive patients. The research method uses a cross-sectional correlation analysis approach carried out in the Bangkalan Regency City Health Center Work Area - Indonesia. The population was 68 patients, and the sample size was 55 respondents taken using simple random sampling. Data were processed using the Spearman Ranks Test with alpha (α) 0.05. The research results show a p value of 0.004 with a correlation coefficient of 0.384, which means there is a positive relationship between strengthening resilience and balancing psychological stress with moderate closeness. Resilience is able to regulate the balance of psychological stress which has an impact on the activation of the neuro-endocrine system to control blood pressure in hypertensive patients.